Risk or resilience? The role of trade integration and foreign ownership for the survival of German enterprises during the Crisis 2008 - 2010 - Joachim Wagner; John P. Weche Gelübcke (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
This is the first study of the link between internationalization and firm survival during the 2008/2009 crisis in Germany, a country which was hit relatively lightly compared to other countries. Moreover, it is the first study which looks at the role of importing, exporting and FDI simultaneously in the context of a global economic recession. We use a tailor-made representative dataset that covers all enterprises from the manufacturing sector with at least 20 employees. Our most striking result is to demonstrate the disadvantage of exporting for the chances of survival of a firm during the crisis in western Germany. Importing instead reveals a positive correlation with survival and firms that both export and import do not show a different exit risk relative to non-traders. A plausible explanation is that in a global recession, deteriorating markets abroad cause demand losses for exporters and improved conditions on factor markets which result in an advantage for firms sourcing from factor markets abroad. Two-way traders do not show a link with exit risk, supporting the idea that they were able to outweigh their losses from exporting with their gains from importing, in what could be called an export-import hedge. Furthermore, we cannot support the hypothesis that foreign multinationals are more volatile during times of economic crisis.
Keywords: F23; L60; 330; Exports; imports; foreign ownership; firm survival; economic crisis; Germany